Root cause analysis of premature simulated life cycle failure of friction stir welded aluminum 2219. (April 2022) - Demeneghi, Gabriel; Rodgers, Kristina; Hua Su, Ching; Medders, William M.; Gorti, Sridhar; Wilkerson, Ryan
Highlights: Friction stir welded aluminum 2219-T62 to 2219-T87 resulted in a premature failure. A series of diagnostic techniques were used to characterize the specimens. Chemical characterization did not present abnormalities near the fracture surface. Hardness and DSC analysis concluded that HAZ is the weakest region on the weld. A featureless fracture was observed, which corresponds to a weak bond on the weld. Second weld pass left unconsumed material from first pass, acting as stress concentrators. Abstract: Aluminum 2219-T62 and aluminum 2219-T87 plates were friction stir welded (FSW) together for a simulated service life test. The test specimen experienced a premature failure after being cycled an order of magnitude lower than expected, from over 30, 000 cycles to 3226 cycles. The failed specimen was investigated through optical microscopy, scanning electron microscopy (SEM), micro-hardness, and differential scanning calorimetry (DSC) to pinpoint the origin of the weakness. It was observed that the failure occurred in the interface between the weld nugget and the aluminum T62, which corresponded to the lowest hardness throughout the weld. Additionally, through fractography of the fracture surface and microstructure investigation of the weld cross-section, it was concluded that a lack of bonding between the weld nugget zone (WNZ) and the base material (BM) coupled with stress concentrators originating from unconsumed material from the first weld pass were the primary factors contributing to the premature failure of the specimen.